On-site calibration of instruments in the Arctic: assessment of temperature records at Climate Change Tower in Ny-Ålesund, Svalbard - Graziano Coppa; Chiara Musacchio; Francesca Becherini; Mauro Mazzola; Angelo Viola; Andrea Merlone (Arctic Science)
The Arctic is as a key place to perform environmental measurements given its combination of reduced human activity and increased sensitivity to climate change. The Svalbard archipelago constitutes an invaluable measurement location, due to its ease of access and the presence of the Ny-Ålesund research center. Sensors are usually not designed to sustain prolonged periods of time in demanding environments like the Arctic; therefore, chances of failures, drift, and errors are higher than elsewhere. Maintenance and calibration of these sensors must be rigorous and frequent, to avoid poor-quality data, or even their loss. Within the frame of EURAMET EMRP project “MeteoMet 2”, calibration of the temperature sensors hosted by the Climate Change Tower (CCT), a unique research facility designed to monitor lower-atmosphere profiles of several meteorological quantities, has been performed. The calibration campaign pointed out sensor errors up to 1 °C and corrected the measurements, straightening the skewed temperature profiles. Absolute calibration uncertainties have been evaluated at ∼0.2 °C, less than half of those stated by the manufacturer, while an evaluation of relative uncertainties yielded values of just few 0.01 °C. This experience stimulated the creation of an in-situ calibration facility, to the benefit of the whole scientific community based in Ny-Ålesund.